IS MOBILE PHONE BAD FOR KIDS? EVIDENCE FROM THE INDONESIAN FAMILY LIFE SURVEY - Esa Azali Asyahid (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
Over the past decade, the use of mobile phones among children has become increasingly prevalent, extending even to those from lower socioeconomic backgrounds. This trend has prompted growing concern regarding the potential adverse effects of mobile phone use on children’s development and well-being. This study aims to provide empirical evidence of the effect of phone ownership and usage among school-age children under 15 years old on their cognitive ability. The primary dataset used in this study is the fifth wave of the Indonesian Family Life Survey (IFLS). To estimate causal relationships, this study employs household fixed effects and an instrumental variable (IV) approach to address selection bias and other sources of endogeneity. The results indicate that, after controlling for household fixed effects, this study does not find statistically significant associations between mobile phone ownership or usage among children and cognitive outcomes, as measured by fluid and crystallized intelligence. The instrumental variable estimates also fail to detect a statistically significant causal effect.